Is Inhibition of Return Modulated by Involuntary Orienting of Spatial Attention: An ERP Study - Pan, Fada; Wu, Xiaogang; Zhang, Li (Frontiers in Psychology, 2017)
Inhibition of return (IOR) is a mechanism that indicates individuals’ faster responses or higher accuracy to targets appearing in the novel location relative to the cued location. According to the “reorienting hypothesis,” disengagement from the cued location is necessary for the generation of IOR. However, more and more studies have questioned this theory because of dissociation between voluntary or involuntary spatial orienting and the IOR effect. To further explore the "reorienting hypothesis" of IOR, the present experiment employed an atypical cue-target paradigm which combined a spatially non-predictive peripheral cue that was presumed to trigger IOR with a spatially non-predictive central cue that was used to reflexively trigger a shift of attention. The results showed that a significant IOR effect did not interact with automatic spatial orienting as measured in mean RTs and accuracy as well as the Nd component. These findings suggested that the IOR effect triggered by peripheral cue was independent of automatic orienting generated by a central cue. Therefore, the present study provided evidence from location task and neural aspects, which again challenged the “reorienting hypothesis” of IOR.